Role of Preprocedural Computed Tomography in Transcatheter Aortic Valve Implantation - Lehmkuhl, L.; Foldyna, B.; Haensig, M.; von Aspern, K.; Lücke, C.; Andres, C.; Grothoff, M.; Riese, F.; Nitzsche, S.; Holzhey, D.; Linke, A.; Mohr, F.-W.; Gutberlet, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Transcatheter aortic valve implantation (TAVI) is currently considered an acceptable alternative for the treatment of patients with severe aortic stenosis and a high perioperative risk or a contraindication for open surgery. The benefit of TAVI significantly outweighs the risk of the procedure in patients requiring treatment that are not suitable for open surgery, and leads to a lower mortality in the one-year follow-up. The absence of a direct view of the aortic root and valve remains a challenge for the transcatheter approach. While direct inspection of the aortic valve during open surgery allows an adequate prosthesis choice, it is crucial for TAVI to know the individual anatomical details prior to the procedure in order to assure adequate planning of the procedure and proper prosthesis choice and patient selection. Among the imaging modalities available for the evaluation of patients prior to TAVI, computed tomography (CT) plays a central role in patient selection. CT reliably visualizes the dimensions of the aortic root and allows a proper choice of the prosthesis size. The morphology of the access path and relevant comorbidities can be assessed. The present review summarizes the current state of knowledge regarding the value of CT in the evaluation of patients prior to TAVI.Key Points:Citation Format:
Keywords: aorta; aortic valve; heart; CT; percutaneous